The Effects of Victimization and Fear of Crime on the Legal Socialization of Young Adolescents in São Paulo, Brazil - Medina, Justin C. (International journal of offender therapy and comparative criminology, 2019)
It is important to understand how young adolescents come to view authorities during formative years. Experiencing, witnessing, and fearing victimization have been linked to the process of legal socialization and subsequent attitudes and behavior. In addition, procedural justice may influence adolescent perceptions of fairness of the authorities. The present study tested whether procedural justice mediated and moderated the relationship between young adolescents' direct and vicarious victimization and developing a sense of legitimacy in authority and cynicism towards authority. A longitudinal sample of 800 Brazilian students, age 11 to 12, living in São Paulo was used to fit structural equation models to examine these relationships. The findings revealed a partial link between victimization and legal socialization. The overall mediating model significantly predicted the direct and indirect relationships between victimization and fear of crime and the formation of legitimacy and cynicism. The moderating effect of procedural justice on direct victimization also significantly predicted the formation of legitimacy. Implications and future research directions are discussed.